2015
DOI: 10.1016/j.neuron.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate-Induced AMPA Receptor Desensitization Increases Their Mobility and Modulates Short-Term Plasticity through Unbinding from Stargazin

Abstract: Short-term plasticity of AMPAR currents during high-frequency stimulation depends not only on presynaptic transmitter release and postsynaptic AMPAR recovery from desensitization, but also on fast AMPAR diffusion. How AMPAR diffusion within the synapse regulates synaptic transmission on the millisecond scale remains mysterious. Using single-molecule tracking, we found that, upon glutamate binding, synaptic AMPAR diffuse faster. Using AMPAR stabilized in different conformational states by point mutations and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
167
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(190 citation statements)
references
References 45 publications
16
167
2
Order By: Relevance
“…Therefore, potential activity-dependent structural rearrangement of the CTD may be of importance for regulation of AMPAR function. Furthermore, it is interesting to note that recent work has shown that pushing synaptic AMPARs into different conformational states influences their mobility (50). Activity-dependent interaction with the membrane or other proteins through the CTD could alter lateral diffusion, consistent with observed effects related to receptor desensitization.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Therefore, potential activity-dependent structural rearrangement of the CTD may be of importance for regulation of AMPAR function. Furthermore, it is interesting to note that recent work has shown that pushing synaptic AMPARs into different conformational states influences their mobility (50). Activity-dependent interaction with the membrane or other proteins through the CTD could alter lateral diffusion, consistent with observed effects related to receptor desensitization.…”
Section: Discussionsupporting
confidence: 58%
“…1D). The positive allosteric modulator cyclothiazide (CTZ) and the competitive antagonist 6,7-dinitroquinoxaline-2,3-dione (DNQX) were characterized independently at the functional GluA2-CFP/YFP constructs expressed in oocytes, along with determination of glutamate EC 50 (Fig. S2 and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, dynamic AMPAR-TARP interactions have also been recently demonstrated to underlie by ability of AMAPRs to support high-frequency stimulation despite undergoing desentisiation 117 . A general consensus is that agonist binding reduces AMPAR affinity for Stargazin 98,117,118 (but see 119,120 ) allowing AMPARs to diffuse away from the synaptically-anchored Stargazin. This loss of desensitised AMPARs from the postsynaptic density frees up 'slots' for non-desensitised AMPARs, which maintains synaptic transmission 117 .…”
Section: Ampar Auxiliary Subunitsmentioning
confidence: 99%
“…A large body of work has demonstrated that Stargazin, and other Type I TARPs (γ3, γ4 and γ8), can promote synaptic trapping of AMPARs through binding to PSD95 and, as discussed above, this interaction offers an attractive mechanism for how AMPARs are recruited and accumulated at the postsynapse during LTP 33, 98 . Furthermore, dynamic AMPAR-TARP interactions have also been recently demonstrated to underlie by ability of AMAPRs to support high-frequency stimulation despite undergoing desentisiation 117 . A general consensus is that agonist binding reduces AMPAR affinity for Stargazin 98,117,118 (but see 119,120 ) allowing AMPARs to diffuse away from the synaptically-anchored Stargazin.…”
Section: Ampar Auxiliary Subunitsmentioning
confidence: 99%
See 1 more Smart Citation